Znaczenie odciętych głów w obrzędowości pogańskiej wczesnośredniowiecznych Słowian zachodnich - Kajkowski, Kamil (Studia mythologica Slavica, 2014)
The author of this paper analyses the sources of the early medieval Western Slavs that point to the existence of the beliefs that connected heads with the essence of the life - the spirit/soul, and considered the head as the most important part of the human body, also possessing a mediatory nature. The head was believed to encompass the most significant aspects of human personality and individual skills. It could also have had supernatural qualities that were manifested through its ability to speak, give advice, warn against danger or foresee the future. This article presents the results of the investigations on the role of the head in Slavic societies and offers new hypotheses.
Keywords: mitologija; mythology; Slavs; Slavs mythology; Slovani; verovanja; beliefs; obredi; rituals